From the Subjected Subject to the Vulnerable Subject: An Unfinished Discussion in Contemporary Spanish Feminisms. - Martinez, Maria (Signs: Journal of Women in Culture & Society)
This article focuses on the subject of feminism in the specific context of contemporary Spain. During the 1970s and 1980s, the feminist movement took as its subject the “woman-housewife-mother,” originally defined by the Franco regime, as a counterpoint from which to propose both an alternative identity for women and a collective identity for the movement. Starting at the end of the 1980s and throughout the 1990s, lesbian-feminists, transgender people, young activists, and queer feminists critiqued the focus on the woman-housewife-mother as the singular subject of feminism. Despite those criticisms, this article—which is drawn from two sociological research projects—notes that some feminists are proposing a new unitary subject of feminism: the vulnerable subject. These feminisms construct this subject using a very narrow conception of vulnerability; vulnerability is exclusively exposure to violence and is equated with femininity. The text concludes with a reflection on how a more open, ambivalent, and ambiguous conception of vulnerability may allow us to rethink the subject of feminism, not by denying vulnerability but by taking it as its condition of possibility.